PENERAPAN METODE SERVQUAL TERHADAP KUALITAS LAYANAN SISTEM INFORMASI MOBILE BANKING PADA BANK JAMBI KCP SUNGAI BAHAR - Muhtadi, Muhammad Amhar; Ikhsan, Muhammad; Marthiawati, Noneng (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2025)
The quality of service provided to create customer satisfaction is a key to success in business competition. Bank Jambi KCP Sungai Bahar must ensure the best service for customer comfort and security. One issue faced is the lack of customer understanding regarding independent mobile banking activation, leading them to rely on customer service assistance. This study uses the Servqual method to measure service quality, with 304 respondents completing a valid questionnaire. Results show the lowest Servqual scores in variables X2.1 and X4.3, while reliability tests indicate that Reliability and Empathy variables have low scores. Indicators in Reliability, such as accessibility and service accuracy, as well as in Empathy, like needed information and customer expectations, were assessed as weak